"Abaixo de Deus eu tenho fé nesses matos”: uma etnografia do regime de cuidado cotidiano entre os Pataxó da aldeia Boca da Mata - Portugal, Larissa Moreira (Universidade Federal de São Carlos, 2022)
This dissertation deals with the daily care regime that Pataxó women from the Boca da Mata village (Barra Velha do Monte Pascoal TI, southern Bahia) operate with the medicinal matos nativos that proliferate in different parts of the territory and, when transformed into remedios de mato, act by quebrando, cortando, desfazendo e matando different ills and diseases that can affect the Pataxó. The objective is to highlight the strong and fundamental feminine and vegetal agencies in Pataxó care practices, as well as to present a description of the multiple domains that the universe of relationalities of these vegetables allow us to access in terms of the ways these people live and be in the world. From “classifications” of the “plant world” to ways of inhabiting the territory and treating terreiros and backyards, notions of disease and health, production of the person and the body, to native theories about blood, aspects of sociability, dreams, the multiple sensory faculties, forms of communication with the auxiliary spirits and, finally, the feminine articulation around the Association of Indigenous Women of aldeia Boca da Mata. It is also proposed to demonstrate how the same matos nativos, which are irreducible agents in daily care practices, were also fundamental for women to face and resist the extraordinary event that consisted of the COVID-19 pandemic. However, it does not intend to conduct an ethnobotanical or ethnopharmacological survey of medicinal plants among the Pataxó, since the proposal, in short, is to offer a description, from the women's point of view, about the universe of relationalities of the medicinal matos with which they make up a unique care regime in the village of Boca da Mata.
"Abaixo de Deus eu tenho fé nesses matos”: a careful ethnography of daily life among the Pataxó of the Boca da Mata village
Keywords: Pataxó; Mulheres; Women; Vegetais; Vegetable; Cuidado; Care; Cotidiano; Daily; Território; Territory; CIENCIAS HUMANAS::ANTROPOLOGIA::ETNOLOGIA INDIGENA; CIENCIAS HUMANAS::ANTROPOLOGIA